Literasi Keuangan, Transformasi Digital dan Perilaku Konsumtif: Perspektif Gender - Riza, Sri Wahyuni; Maresti, Dwila (Syntax Literate, 2025)
This study aims to examine the impact of digital transformation on individual/community consumer behavior, with financial literacy as a moderator. This study will use a descriptive quantitative approach that explains the research results in the form of numbers narratively. The data collection technique through digital platforms to reach a sample of 100 with a total target population of 150 respondents. The sample criteria are individuals/communities who use digital platforms in their financial transactions, especially buying and selling transactions, with an age limit of 17 to 65 years. The results of the study generally indicate that digital platforms have a significant positive effect on consumer behavior, which is dominated by women. However, women who have financial literacy in terms of financial management experience prefer to prioritize their primary needs in their consumer practices amidst offers of attractive facilities and convenience in purchasing transactions. This means that financial literacy moderates consumer behavior, thus having a significant negative effect. The implications of the study emphasize strengthening financial literacy through a digital-based educational and regulatory approach. This will increase individual and community awareness in self-control to spend their money more effectively and efficiently.